Caractéristiques sociodémographiques des minorités visibles - RTS de l'Est-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de l'Est-de-l'Île-de-Montréal.

Caractéristiques sociodémographiques des minorités visibles - RTS de l'Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de l'Ouest-de-l'Île-de-Montréal.

Caractéristiques sociodémographiques des minorités visibles - RTS du Centre-Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS du Centre-Ouest-de-l'Île-de-Montréal.

Caractéristiques sociodémographiques des minorités visibles - RTS du Centre-Sud-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS du Centre-Sud-de-l'Île-de-Montréal.

Caractéristiques sociodémographiques des minorités visibles - RTS du Nord-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS du Nord-de-l'Île-de-Montréal.

Socio-Demographic Characteristics of Visible Minorities in RTS de l'Est-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de l'Est-de-l'Île-de-Montréal.

Socio-Demographic Characteristics of Visible Minorities in RTS de l'Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de l'Ouest-de-l'Île-de-Montréal.

Socio-Demographic Characteristics of Visible Minorities in RTS du Centre-Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS du Centre-Ouest-de-l'Île-de-Montréal.

Socio-Demographic Characteristics of Visible Minorities in RTS du Centre-Sud-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS du Centre-Sud-de-l'Île-de-Montréal.

Socio-Demographic Characteristics of Visible Minorities in RTS du Nord-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS du Nord-de-l'Île-de-Montréal.

RTS de l'Est-de-l'Île-de-Montréal - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de l'Est-de-l'Île-de-Montréal - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de l'Ouest-de-l'Île-de-Montréal - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de l'Ouest-de-l'Île-de-Montréal - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Centre-Ouest-de-l'Île-de-Montréal - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Centre-Ouest-de-l'Île-de-Montréal - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Centre-Sud-de-l'Île-de-Montréal - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Centre-Sud-de-l'Île-de-Montréal - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Nord-de-l'Île-de-Montréal - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Nord-de-l'Île-de-Montréal - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Demographic Profiles of Québec's English-speaking Communities of Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de l'Est-de-l'Île-de-Montréal - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de l'Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS du Centre-Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS du Nord-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Employment Profile of English Speakers in Montréal - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Montréal’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Montréal’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Profil d'emploi des Québécois d'expression anglaise de la Montréal - Provincial Employment Roundtable (PERT) (2022)
Ce profil a pour but de contribuer à la connaissance et à la compréhension des difficultés en matière d’emploi auxquelles font face les communautés de l’expression anglaise de Montréal en analysant les informations les plus complètes sur la démographie et les conditions de travail des personnes d’expression anglaise de la région. Le profil compile les données disponibles sur le statut d’emploi des personnes d’expression anglaise par rapport à leur position de minorité linguistique au sein de communautés majoritairement francophones. Par conséquent, la plupart des informations présentées dans ce profil sont organisées selon ces deux catégories linguistiques; personnes d’expression anglaise et personnes d’expression française. En plus d’examiner les données démographiques et les conditions de travail de la population d’expression anglaise, ce profil analyse la structure économique de Montréal, de même que l’activité professionnelle, le revenu et le niveau d’éducation des travailleurs dans le but d’en dresser un portrait d’emploi et d’employabilité complet.

Harnessing your Transferable Skills in a COVID-19 Economy - Khamala, Maya (2021)

Job Search Mentorship During COVID-19 - Khamala, Maya (2021)

Skill-Building & Networking in the Time of COVID-19 - Khamala, Maya (2021)

[Dashboards - Quebec and RTS Territories] - Community Health and Social Services Network (CHSSN) (2021)

RTS de l'Est-de-l'Île-de-Montréal - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de l'Ouest-de-l'Île-de-Montréal - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS du Centre-Ouest-de-l'Île-de-Montréal - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS du Centre-Sud-de-l'Île-de-Montréal - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS du Nord-de-l'Île-de-Montréal - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

Fall Program Book : September - December 2021 - Youth Employment Services (YES) (2021)

Showing up When it Counts : 2021 Annual Report - Youth Employment Services (YES) (2021)

Toujours au rendez-vous : Rapport annuel 2021 - Youth Employment Services (YES) (2021)

Program Book - Youth Employment Services (YES) (2020)

YES Program Book - Youth Employment Services (YES) (2020)

Job Search in the Time of Covid-19 : Resource Guide for Job Seekers - Youth Employment Services (YES) (2020)

Who We Are - Youth Employment Services (YES) (2020)

Winter/Spring 2020 Program Book : January 2020 - August 2020 - Youth Employment Services (YES) (2020)

Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2019)

Empowering African-Canadian Career Excellence - Community Economic Development and Employability Corporation (CEDEC) (Collaborative Unity and Existential Responsibility, 2019)
The African-Canadian Career Excellence (ACCE) initiative was developed to address the loss of highly-educated, English-speaking Black youth from the Greater Montreal Area (Quebec, Canada) facing issues of unemployment and underemployment.
Keywords: Official Language Minority Community (OLMC)

Tune into Yes 13 : A Benefit Concert & Silent Auction - Youth Employment Services (YES) (2019)
Featuring an impressive silent auction, complimentary food, wine, beer and live entertainment, Tune In To YES is not only an exciting networking and social event, it is also an opportunity to help job-seekers, entrepreneurs and artists in our community.

Community Education and Development : Perspectives on Employment, Employability and Development of English-Speaking Black Minority of Quebec - Bayne, Clarence S (Collaborative Unity and Existential Responsibility, 2019)
On December 7, 2018, the Black Community Forum of Montreal held a conference on “Community Education and Development: perspectives on English-Speaking Blacks and Other Minorities”. The IJCDMS Journal has selected a number of the conference papers for publication in its Special Conference Series: “Collaborative Unity and Existential Responsibility.” This article serves as an overview to the conference; and provides a theoretical framework against which the reader can derive a better understanding of those papers. It allows the reader to reflect meaningfully on the optimality of the decision search rules adopted by various cultural subgroups, by comparing them to the behaviors of successful agent types in the computer simulated studies discussed in this paper. The targeted cultural sub-populations are the English-Speaking Blacks in Montreal.
Keywords: Official Language Minority Community (OLMC)

Program Book for Winter/Spring 2018 - Youth Employment Services (YES) (2018)

Employee Resource Guide - NDG Community Council (NDGCC) (2018)

Guide de ressources d'emploi - NDG Community Council (NDGCC) (2018)

Demographic Profile of the English-speaking Communities : Administrative Region of Montréal & the Rest of Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Job Posting : Events & Access Coordinator - State of the Arts III - English Language Arts Network (ELAN) (2018)

Job Posting : Project Manager - State of the Arts III - English Language Arts Network (ELAN) (2018)

Reisaction Newsletter - Réseau de l’est de l’île pour les services en anglais (REISA) (2018)

Program Book for Winter/Spring 2017 - Youth Employment Services (YES) (2017)

Reisaction Newsletter - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)

Demographic Profiles of English-speaking Communities in RTS de l'Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities in RTS du Centre-Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities in RTS du Centre-Sud-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities in RTS du Nord-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Est-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Est-de-l'Île-de-Montréal & RLS de Hochelaga - Mercier-Ouest - Rosemont (0653) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Est-de-l'Île-de-Montréal & RLS de Rivière-des-Prairies - Anjou - Montréal-Est (0652) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Est-de-l'Île-de-Montréal & RLS de Saint-Léonard - Saint-Michel (0651) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Ouest-de-l'Île-de-Montréal & RLS de Dorval - Lachine - Lasalle (0612) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Ouest-de-l'Île-de-Montréal & RLS de Pierrefonds - Lac Saint-Louis (0611) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Centre-Ouest-de-l'Île-de-Montréal & RLS de Côte-des-Neiges - Métro - Parc-Extension (0622) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Centre-Ouest-de-l'Île-de-Montréal & RLS de Côte-Saint-Luc - NDG - Montréal-Ouest (0621) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Centre-Sud-de-l'Île-de-Montréal & RLS de Verdun - Côte St-Paul - St-Henri - Pointe-St-Charles (0631) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Centre-Sud-de-l'Île-de-Montréal & RLS des Faubourgs - Plateau-Mont-Royal - St-Louis-du-Parc (0632) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Nord-de-l'Île-de-Montréal & RLS d'Ahuntsic - Montréal-Nord (0642) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Nord-de-l'Île-de-Montréal & RLS de la Petite Patrie - Villeray (0643) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Nord-de-l'Île-de-Montréal & RLS du Nord de l'Île - Saint-Laurent (0641) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Fall 2017 : Program Book : September 2017 - December 2017 - Youth Employment Services (YES) (2017)

Program Book for Winter/Spring 2016 - Youth Employment Services (YES) (2016)

Fall 2016: Program Book : September 2016 - December 2016 - Youth Employment Services (YES) (2016)

The East Island Retention of Health Professionals Project – English, An Asset! : REISA Internships - A Success Story - Gatre Guemiri, Fatiha; Zappitelli, Juliana; Mirtaheri, Mina; Granner, Francine; Hendrickson-Nelson, Mary (2015)

African-Canadian Career Excellence : 2015 Employer Survey - Community Economic Development and Employability Corporation (CEDEC) (2015)
This report provides the final data analysis and interpretation of the 2015 employer survey on the hiring norms and practices of businesses across various sectors and industries in the Greater Montreal area, with a focus on employers’ attitudes towards the importance of a having a diverse workforce. This study is part of the African-Canadian Career Excellence (ACCE) initiative aimed at countering the migration of Black graduates from Montreal.

African-Canadian Career Excellence : 2014 Student Survey : The Needs and Challenges of Education Black Youth in Obtaining Meaningful and Sustainable Employment - Community Economic Development and Employability Corporation (CEDEC) (2015)

Initiative pour l'excellence de la carrière des Afro-Canadiens : Enquête réalisée en 2014 : Les besoins et les défis auxquels font face les jeunes de race noire pour obtenir un emploi rémunérateur et durable - Community Economic Development and Employability Corporation (CEDEC) (2015)
Ce rapport présente l’analyse et l’interprétation de l’enquête réalisée auprès des étudiants du premier cycle universitaire en 2014 sur leurs perceptions de la transition vers l’emploi à Montréal. Ce résumé, une étape réalisée par l’Initiative pour l’Excellence de la carrière des Afro-Canadiens œuvrant à contrer la migration des jeunes diplômés noir montréalais, vise à influencer la conception de formations s’adressant aux jeunes diplômés afin de faciliter le lancement de leur carrière et la progression de celle-ci au Québec.

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2014)

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2014)

Winter/Spring 2014 Program Book - Youth Employment Services (YES) (2014)

African-Canadian Career Excellence : Undergraduate Survey 2011-2012 Summary Report - Community Economic Development and Employability Corporation (CEDEC) (2013)
This summary report provides the final data analysis and interpretation of the 2011-2012 undergraduate student survey on perceptions of transition to employment in Montreal. As one step in the African-Canadian Career Excellence (ACCE) initiative aimed at countering the migration of Black graduates from Montreal, this summary will inform the design of development training for young graduates to facilitate their career launch and advancement in Quebec. Information and insights herein were provided by the following members of ACCE: Dorothy W. Williams of the Black Community Resource Centre (BCRC), Dwight Best of the African and Caribbean Students’ Network of Canada (ACSioN), Tamara Hart of the Tyndale St-Georges Community Centre, Velda Bourne, Karima West, and Nina Kim and Larissa Milo-Dale of the Community Economic Development and Employability Corporation (CEDEC). Preliminary data analysis and interpretation were contributed by Jan Warnke J W COMM INC.

Initiative pour l'excellence de la carrière des Afro-Canadiens : Sondage réalisé auprès des étudiants du premier cycle universitaire - Community Economic Development and Employability Corporation (CEDEC) (2013)
Ce rapport sommaire consigne les résultats et l'interprétation de l'analyse des données du sondage réalisé auprès des étudiants au premier cycle universitaire de 2011-2012 sur leurs perceptions de la transition vers le marché du travail de Montréal. Comme l’une des démarches de l'Initiative pour l’Excellence de la carrière des Afro-Canadiens consiste à contrer la migration des diplômés noirs de Montréal, ce rapport influencera l'élaboration de formations de perfectionnement pour les jeunes diplômés afin de faciliter l’amorce de leur carrière et leur progression professionnelle au Québec.

Building Youth Resiliency and Community Vitality Within Montreal’s English Language Population : The YES Experience with Youth Seeking to Improve their Work Situation - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2013)
In response to an increase in the number of clients’ experiencing mental health challenges in the course of their job search YES (through CHSSN) has commissioned this report to establish an evidence-based profile of the youth that they serve. At the present time, YES uses limited resources to offer additional support through a focus group that is designed for clients who are experiencing symptoms such as decreased motivation, anxiety, social isolation and diminished confidence in dealing with the transition process.
Keywords: Official Language Minority Community (OLMC)

Program Book - Youth Employment Services (YES) (2013)

Winter/Spring 2013 Program Book - Youth Employment Services (YES) (2013)

YES' Artists' Conference: Business Skills for Creative Souls - Youth Employment Services (YES) (2013)

Regional Development of English Language Entrepreneurial Services - Qu'anglo (Youth Employment Services (YES), 2012)
YES is a non-profit organization that provides English language employability and entrepreneurship services in Quebec, principally those on the Island of Montreal. The areas of services offered are job search, entrepreneurship, mentorship and artists’ programs. In response to requests from the organizations in the regions outside of Montreal for similar services, YES has begun to develop support and delivery mechanisms that respond to the unique needs of the regions1 within a context of building economic viability. This report provides the results of the work carried out in 2011-12 to look at the feasibility of offering YES-type services in the regions, as well as the planning and development activities that should be carried out to support a broader economic development amongst English-speaking communities in Quebec.
Keywords: Official Language Minority Community (OLMC)

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2012)

Helping Montreal's Youth into the Workforce - Youth Employment Services (YES) (2011)

Young Quebec Artists Encouraged to Turn their Passion into Profit - Youth Employment Services (YES) (2011)

9th Quebec Employment Service Providers Conference : The Greatest Challenges and Best Practices of Employment Service Professionals - Youth Employment Services (YES) (2011)

Youth Employment Services Celebrates 35,000 Served, 15 Years Strong - Youth Employment Services (YES) (2010)

YES Montreal Kicks Off its Summer Job Campaign : Close to 1000 Available Positions - Youth Employment Services (YES) (2010)

YES Montreal Helps Entreprenuers Capitalize on Opportunities at the 13th Annual Entrepreneurship Conference : Made in Montreal - Youth Employment Services (YES) (2010)

With the Help of YES, the Creative Workforce Turns Passion into Profit : Premières To Showcase Emerging Artists - Youth Employment Services (YES) (2010)

The YES Holiday Job Rush Campaign : Getting Montreal's Youth into the Workforce - Youth Employment Services (YES) (2009)

Getting Motivated & Staying Focused - Youth Employment Services (YES) (2009)

YES E-Newsletter : June 2009 - Youth Employment Services (YES) (2009)

YES E-Newsletter : May 2009 : Volume 1 : Issue 5 - Youth Employment Services (YES) (2009)

YES E-News : April 2009 - Youth Employment Services (YES) (2009)

Transformation Through Lifelong Learning: A Path to Change - Quebec Association for Adult Learning (QAAL) (2009)

Dialogue : Better Communication for Better Care - Dialogue McGill (2009)

Dialogue : Mieux communiquer pour mieux soigner - Dialogue McGill (2009)

Winter/Spring 2009 Program Book - Youth Employment Services (YES) (2009)

Congrès des Fournisseurs de Sercices d'emploi du Québec (2008)

Quebec Employment Service Providers Conference (2008)

The 11th YES Entrepreneurship Conference : March 8/2008 - Youth Employment Services (YES) (2008)

Stepping into the Future : L’avenir entre nos mains - Carrefour jeunesse-emploi NDG; Table de concertation jeunesse NDG (NDG Community Council (NDGCC), 2008)
Community‐based planning to facilitate the socio‐professional integration of youth between the ages of 16 ' and 30 in Notre‐Dame‐de‐Grâce, Côte‐Saint‐Luc, Hampstead and Montreal‐West. A project of the Carrefour jeunesse‐emploi NDG and the Table de concertation jeunesse NDG, in collaboration with Service Canada

Dialogue : Better Communication for Better Care - Dialogue McGill (2008)

Dialogue : Mieux communiquer pour mieux soigner - Dialogue McGill (2008)

Fall 2008 Program Book - Youth Employment Services (YES) (2008)

Winter/Spring 2008 Program Book - Youth Employment Services (YES) (2008)

YES E-News : September 2007 - Youth Employment Services (YES) (2007)

Discussion Document #1 : Demographics and the Long-term Development of the English-speaking Communities of the Greater Montreal Region - Quebec Community Groups Network (QCGN); Greater Montreal Community Development Initiative (GMCDI) (2007)

The 10th Anniversary YES Entrepreneurship Conference : March 3/2007 - Youth Employment Services (YES) (2007)

Dialogue : Better Communication for Better Care - Dialogue McGill (2007)

Dialogue : Mieux communiquer pour mieux soigner - Dialogue McGill (2007)

Report of the Greater Montreal Community Development Initiative Steering Committee : Building Upon Change and Diversity within the English-speaking Communities of the Greater Montreal Region: - Greater Montreal Community Development Initiative (GMCDI) (Quebec Community Groups Network (QCGN), 2007)
In the 30 years since the passage of Bill 101, the nature of the English-speaking communities of the Greater Montreal Area has changed dramatically. The evolution of the largest linguistic minority within a linguistic minority in Canada has resulted in the emergence of certain unique challenges and opportunities. It was to address these issues that the Greater Montreal Community Development Initiative (GMCDI) was launched. This initiative, funded by the Department of Canadian Heritage, is intended to assist the English-speaking communities of the Greater Montreal Area in identifying shared community development challenges and priorities, and the most effective strategies to address them.
Keywords: Official Language Minority Community (OLMC)

Program Book: Winter / Spring 2007 - Youth Employment Services (YES) (2007)

BCRC Newsletter - Black Community Resource Centre (BCRC) (2006)

6th Montreal Self-Employed Artists Conference - Youth Employment Services (YES) (2006)

BCRC Newsletter - Black Community Resource Centre (BCRC) (2005)

BCRC Newsletter - Black Community Resource Centre (BCRC) (2005)

Job Hunting Tips for Introverts - Khamala, Maya

The "Candidate Experience" Evaluation the Hiring Process - Khamala, Maya

Mental Health and the Work Place : It's Okay to Not Feel Okay - Morgenstern-Clarren, Rachel

“Tell Me About Yourself" : How to Answer the Hardest Interview Question - Morgenstern-Clarren, Rachel

Jump Start Your Job Search : Readiness Questionnaire - Youth Employment Services (YES)

Making your Job Search Work for You - Youth Employment Services (YES)

The 10th Annual YES Entrepreneurship Conference : YES, The Future is Yours : Workshops - Youth Employment Services (YES)

The 19th Annual Entrepreneurship Conference - Youth Employment Services (YES)

YES E-News Monthly - Youth Employment Services (YES)